2008
DOI: 10.1111/j.1747-0285.2008.00735.x
|View full text |Cite
|
Sign up to set email alerts
|

Exploring QSAR for Substituted 2‐Sulfonyl‐Phenyl‐Indol Derivatives as Potent and Selective COX‐2 Inhibitors Using Different Chemometrics Tools

Abstract: Selective inhibition of cyclooxygenase-2 inhibitors is an important strategy in designing of potent anti-inflammatory compounds with significantly reduced side effects. The present quantitative structure-activity relationship study, attempts to explore the structural and physicochemical requirements of 2-sulfonyl-phenyl-indol derivatives (n = 30) for COX-2 inhibitory activity using chemical, topological, geometrical, and quantum descriptors. Some statistical techniques like stepwise regression, multiple linear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 50 publications
1
8
0
Order By: Relevance
“…However, the use of specific COX-2 selective drugs was a failure owing to their cardiovascular side effects that occurred because of the inhibition of prostaglandins secretion which is required for the normal functioning of the cardiovascular system and is produced by COX-1 isoform [3].…”
Section: Introductionmentioning
confidence: 99%
“…However, the use of specific COX-2 selective drugs was a failure owing to their cardiovascular side effects that occurred because of the inhibition of prostaglandins secretion which is required for the normal functioning of the cardiovascular system and is produced by COX-1 isoform [3].…”
Section: Introductionmentioning
confidence: 99%
“…Khoshneviszadeh et al. modeled COX‐2 inhibitory activity using Petitjean index along with other molecular descriptors …”
Section: Resultsmentioning
confidence: 99%
“…As a solution to this limitation for example in PCA, using of the loadings of the selected principal components has been suggested to obtain the variables of high loading values [325,326]. Also, instead of application of feature extraction methods on whole data set, Hemmateenejad et al suggested partitioning of variables into different subsets firstly and then running of PCA on each subset, separately.…”
Section: Dimension Reduction and Feature Extractionmentioning
confidence: 99%